2011
DOI: 10.1007/s12355-011-0075-3
|View full text |Cite
|
Sign up to set email alerts
|

Physico-Chemical Method of Preserving Sucrose in Harvested Sugarcane at High Ambient Temperature in a Sub-Tropical Climate

Abstract: Sugarcane in subtropical areas is harvested under a wide array of temperatures, grading from 8 to 42°C. The crushing of harvested cane is often delayed for longer than 72 h leading to a steep decline in sucrose content, especially late in the harvest season when ambient temperatures are high. The average reductions in Commercial Cane Sugar (CCS) in untreated billets and whole cane during late harvest were 0.735 and 0.502 units/day. These losses were reduced to 0.310 and 0.365 units/day following treatment with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 10 publications
2
12
0
Order By: Relevance
“…Considering results against controls, BKC + SMS formulation and sodium chloride was found to be as effective as formaldehyde and glutaraldehyde. Similar results were also observed by this chemical formulation in another study on freshly harvested canes under normal conditions [ 30 ] and under drought conditions [ 16 ] due to their synergistic effect of anti-bacterial and anti-inversion property. This might be the reason behind the strong zone of inhibition in our study against this bacterium.…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…Considering results against controls, BKC + SMS formulation and sodium chloride was found to be as effective as formaldehyde and glutaraldehyde. Similar results were also observed by this chemical formulation in another study on freshly harvested canes under normal conditions [ 30 ] and under drought conditions [ 16 ] due to their synergistic effect of anti-bacterial and anti-inversion property. This might be the reason behind the strong zone of inhibition in our study against this bacterium.…”
Section: Resultssupporting
confidence: 86%
“…In harvested canes, presence of acid and neutral invertases has been reported in north Indian states where cane deterioration is uncontrollable [ 64 ]. Acid invertase activity in harvested canes is a quality decreasing indicator [ 30 ]. Increase in acid invertase activity as well as endogenous and exogenous microbial activity with increase in delay in crushing has been evident in number of studies for sucrose losses occurring in harvested canes [ 65 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies on sugarcane (Saccharum officinarum L.) and sweet sorghum reported that biomass pressing should be initiated soon after harvest to prevent deterioration of soluble sugars [14][15][16]. Wu et al [10] have reported that a 20 % loss of fermentable sugars in sweet sorghum juice will occur after 3 days of storage at room temperature and 50 % after 1 week.…”
Section: Introductionmentioning
confidence: 99%